Wykorzystanie narzędzi pomiaru dydaktycznego jako przejaw nowatorstwa pedagogicznego w wybranych pracach dyplomowych - Derenowski, Marek (Rocznik Pedagogiczny, 2021)
Evaluating students’ work has always been a challenging undertaking. The objectivity and reliability of instruments may sometimes be doubtful. Therefore, the aim of the study described in the paper was to analyze possible innovative behaviors/activities among MA students/teachers/researchers in the field of assessment described in their MA thesis. It is intriguing to find out whether future and present educators take the effort (and risk) of introducing some improvements in this crucial educational field.